Avaliação do impacto da telemedicina no manejo do infarto agudo do miocárdio: revisão sistemática e metanálise. - Luciana Marques Maia (2016)
Introduction: Telemedicine strategies have the potential to increase healthcare professionals adherence to the therapeutic measures established for acute myocardial infarction (MI), to improve MI care. However, the real impact of this intervention in clinical outcomes is still unknown or poorly documented. The objective of this study is to conduct a systematic review and meta-analysis of studies assessing the impact of telemedicine interventions combined with usual care compared to usual care alone on AMI mortality and time of reperfusion. Methods: Eight literature databases including Google Scholar were searched to identify relevant studies published from Jan/2004 to May/2015. The search was supplemented by references from the selected articles. Study search and selection were performed by independent reviewers. Methodological quality of non-randomized studies was assessed by Newcastle Ottawa scale (NOS) and GRACE (Good ReseArch for Comparative Effectiveness) checklist. Random effects model was applied to estimate the pooled results of primary outcomes (in hospital, 30 day and one year mortality) and secondary outcomes (time of AMI reperfusion, left ventricular ejection fraction and length of stay). We evaluated publication bias, sensivity analysis, heterogeneity (I2) and subgroup analysis. Results: Of the 5.407 articles retrieved, 33 studies (21622 patients) were included: 11 in Europe, 14 in North America, 3 in South America and 5 in Asia. No randomized controlled trial was identified; 27 studies were nonrandomized controlled, 8 historically controlled, and 4 quasi-experimental. The studies were classified as moderate to high quality by NOS and GRACE. Telemedicine was associated with a statistically significant reduction in in-hospital mortality (12 studies [n=6033], risk ratio [RR] 0.54 [CI 95% 0.46-0.64], I2<0.01%, no evidence of publication bias, risk difference [RD] -0,05, [IC 95% -0,07- 0,04], p<0,0001, NNT 19 [IC95% 14 a 25]), 30-day mortality (5 studies [n=3506], RR 0.67 [CI 95% 0.49-0.95], I2 23%, no evidence of publication bias DR -0,03, [IC 95% 0,053- -0,003], NNT 36 [IC95% 16 a 142]). The statistical significance was obtained after a study exclusion in one-year mortality (3 studies [n=1549], RR 0.47 [IC 95% 0.33-0.68], I2<0.01%, DR -0,09, [IC 95%-0,164 --0,022], NNT 11 [IC95% 6 a 45]). In sensitivity analyses, studies were individually omitted from the meta-analysis, and the RR remained about the same in hospital and 30 day mortality. In secondary outcomes analysis were observed time of AMI reperfusion reduction, with large heterogeneity, length of hospital stay reduction and improved left ventricular function with moderate heterogeneity.Conclusions: Telemedicine strategies combined with the usual care for MI patients are associated with reduction in reperfusion AMI delay and reduction in-hospital, 30-day and one-year mortality.